Transplante de membrana amniótica para tratamento do pterígio recidivado - Bruni, Ligia Fernanda [UNESP]; Schellini, Silvana Artioli [UNESP]; Jaqueta, Elisângela [UNESP]; Kamegasawa, Amélia [UNESP]; Padovani, Carlos Roberto [UNESP] (My University, 2001)
Purpose: To evaluate the effectiveness of amniotic membrane transplantation for recurrent pterygium treatment. Methods: Amniotic membrane transplantation was performed in 27 eyes with recurrent pterygium, 7 with associated symblepharon. We evaluated age, sex, eye, site, number of previous surgeries and postoperative complications with a follow-up period of 6 months. Results: 58.3% of the patients were male and, 58.3% were between 40 and 59 years old. All of them had recurrent pterygium and 47.8% with at least two previous surgeries. We observed recurrence in 18.5% and 11.1% had granulomatous lesions. Conclusion: Amniotic membrane transplantation is a simple procedure and is a good choice to treat recurrent pterygium. However, this technique does not exclude the possibility to present lesion recurrence.
Amniotic membrane transplantation for recurrent pterygium treatment
Keywords: Amnion/transplantation; Biological dressing/utilization; Ophthalmic surgical procedures; Pterygium/surgery